Bruxism: A literature review (Research, Society and Development, 2024)
Bruxism is considered a parafunction that is related to muscular hyperactivity. It can be classified as a non-spontaneous act, leading to disordered movements of the jaw, causing clenching and grinding of the teeth, thus causing an overload on the stomatognathic system. It causes several aesthetic and functional problems such as: tooth wear, headaches, neck and face pain, tooth sensitivity, malocclusion, loss of tooth and bone structure, which can lead to periodontal disease.  Its classifications are between daytime (wakefulness) and nighttime (sleep), according to the damage to the stomatognathic system, and between primary and secondary. The etiology is still doubtful and inconclusive today, there are several factors that end up triggering bruxism. The objective of this work is to report the clinical characteristics of bruxism, diagnosis, etiology and existing treatments through a narrative review of the literature.  Research shows us that the cause would be multifactorial, where the factors reported by most authors are divided into three large groups: psychological factors, peripheral factors and pathophysiological factors. The clinician must know how to evaluate the clinical signs, with a detailed anamnesis and a careful physical examination, in order to have a correct diagnosis. Muscle hypertrophy and wear on the incisal edges may be signs that the pathology is present. Treatment is usually multidisciplinary and may involve a dentist, psychologists and doctors.